Matching and challenge gifts to charity: evidence from laboratory and natural field experiments - Daniel Rondeau; John A. List (Institute for the Study of Labor (IZA), 2008)
This study designs a natural field experiment linked to a controlled laboratory experiment to examine the effectiveness of matching gifts and challenge gifts, two popular strategies used to secure a portion of the 200 billion annually given to charities. We find evidence that challenge gifts positively influence contributions in the field, but matching gifts do not. Methodologically, we find important similarities and dissimilarities between behavior in the lab and the field. Overall, our results have clear implications for fundraisers and provide avenues for future empirical and theoretical work on charitable giving.
Keywords: C93; 360; Charitable giving; threshold public goods; fundraising; field experiments; Wohltätigkeit; Spendensammlung; Privater Transfer; Gemeinnützigkeitsrecht; Konditionen; Wohlfahrtseffekt; Test; USA